The Ironic Privacy Act - Margaret Hu (Washington University Law Review, 2019)
This Article contends that the Privacy Act of 1974, a law intended to engender trust in government records, can be implemented in a way that inverts its intent. Specifically, pursuant to the Privacy Act’s reporting requirements, in September 2017, the U.S. Department of Homeland Security (DHS) notified the public that record systems would be modified to encompass the collection of social media data. The notification justified the collection of social media data as a part of national security screening and immigration vetting procedures. However, the collection will encompass social media data on both citizens and noncitizens, and was not explicitly authorized by Congress. Social media surveillance programs by federal agencies are largely unregulated and the announcement of social media data collection pursuant to the reporting requirements of the Privacy Act deserves careful legal attention. Trust in the Privacy Act is at risk when the Act’s notice requirements announce social media data collection and analysis systems under the guise of modifying record collection and retention protocols. This Article concludes that the social media data collection program proposed by DHS in September 2017 requires express legislative authorization.
Keywords: Privacy Act of 1974; Social media surveillance; Federal surveillance; National security screening; Legislative authorization; Extreme vetting